Fetal Mummification in a Doe: A Comparative Case Study - Narwade, Priyanka; Jena, Dayanidhi; Ravi, Sanjay Kumar; B.Balamurugan; Mishra, Rabindra Mohan; Kadam, Rahul G (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Fetal mummification is a condition where there is death of the conceptus followed by resorption of fetal fluids and the uterus wraps around the fetus tightly giving an impression of ‘mummy’. In this case reports, two different cases of fetal mummifications in goats over a period of one year was observed at the Teaching Veterinary Clinical Complex, Faculty of Veterinary and Animal Sciences, Rajiv Gandhi South Campus, Banaras Hindu University, Barkachha, Mirzapur. The detailed management and treatments are discussed in this short communication.